Special Issue: “Biophysics, Arrhythmias and Pacing” - Matteo Bertini (Biology, 2023)
Cardiac pacing technologies have been implemented during the last few decades, including leadless pacemakers and pacing of the conduction system, such as His bundle pacing and left bundle branch area pacing [...]